'Doing for group exercise what McDonald's did for hamburgers': Les Mills, and the fitness professional as global traveller. Issue 2 (17th February 2016) - Andreasson, Jesper; Johansson, Thomas
Abstract : This article analyses fitness professionals' perceptions and understanding of their occupational education and pedagogical pursuance, framed within the emergence of a global fitness industry. The empirical material consists of interviews with personal trainers and group fitness instructors, as well as observations in their working environment. In addition, printed material from different occupational organisations and educational companies has been included. The narratives of the fitness professionals and a case study of Les Mills are presented and analysed through the concept of the McDonaldisation of society, or more specifically of fitness culture. The results show that, even though gym and fitness franchises differ from hamburger restaurant chains, there are crucial similarities, but also differences. One can, for example, discern a tendency towards the construction of predesigned and highly monitored programmes, such as the one developed by Les Mills. Homogenisation is also apparent when looking at the body ideals produced, as fitness professionals work on their own or clients' bodies, which makes it possible to anticipate a global body ideal. The social and cultural patterns of self-regulation and self-government found in gym and fitness culture can be understood and analysed in a global context. What we find is an intriguing and complex mixture of regulation, control and standardisation, on the one hand, and a struggle to express the body, to be 'free' and to transgress the boundaries set by the commercial global fitness industry, on the other.